The Complexity of English Online Learning: English Teachers’ Data-Driven - Riswanto, Riswanto (Journal of Social Work and Science Education, 2023)
The offline-to-online transformation of learning in the new normal era leaves complexity for English teachers. Hence, this qualitative study aimed to uncover the complexity of English online learning in terms of implementation, English teachers’ perspectives, technological tools, problems, causes of the problems, and related solutions. English teacher participants were observed and interviewed, and the data were analyzed interactively. This study revealed that the English teachers executed online learning from planning, and implementation, to evaluation. They perceived English online learning as positive because of its convenience during the condition of Covid-19 outbreak, but they also considered it negative due to their insufficient technical knowledge and experiences. They utilized WhatsApp, email, Google Forms, zoom, Ruang Guru platform, and Instagram as the media. However, they had some problems, such as difficulty in delivering English materials online, difficulty in managing their online classes, and weak internet connections. These problems were caused by the lack of supporting facilities and technological competencies. As solutions, they dynamically chose ideal locations for learning with good internet connections, asked for help from fellow teachers, and metacognitively learned about learning technology from the Internet. Further studies are expected to involve more participants and be conducted with a mixed-method design.